Application of the Discovery Learning Model to Improve Poetry Writing Skills of Grade X Students - Haliza Putri Pramesthi; Adyana Sunanda (Journal of Educational Sciences, 2026)
This study investigates the effectiveness of the Discovery Learning model in improving poetry writing skills among Grade X students at SMA Muhammadiyah 1 Sragen. Poetry writing is often perceived as challenging due to limited student engagement and teacher-centered instructional practices. This research aimed to examine changes in student responses and learning outcomes after the implementation of Discovery Learning in Indonesian language instruction. A qualitative research design was employed using systematic observation, semi-structured interviews, and documentation. Data were analyzed through an interactive model involving data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings reveal that the Discovery Learning model significantly enhanced students’ active participation, learning motivation, critical thinking, and confidence in composing poetry. Students demonstrated greater independence, deeper understanding of poetic elements, and improved collaboration during learning activities. Observations confirmed that all six stages of Discovery Learning were implemented effectively. Although challenges such as time constraints and initial student adaptation were identified, the overall pedagogical benefits outweighed these limitations. The study concludes that Discovery Learning provides meaningful learning experiences and effectively supports the development of creative writing skills within the Merdeka Curriculum framework.